A Short Theoretical Review of Charmonium Production - Chen, An-Ping; Ma, Yan-Qing; Zhang, Hong (Advances in High Energy Physics, 2022)
In this paper, we review the current status of the phenomenological study of quarkonium production in high-energy collisions. After a brief introduction of several important models and effective field theories for quarkonium production, we discuss the comparisons between theoretical predictions and experimental measurements.